Can personality explain what is underlying women’s unwillingness to compete? - Müller, Julia; Schwieren, Christiane (Journal of economic psychology, 2012)
There is ample evidence that women do not react to competition as men do and are less willing to enter a competition than men. In this paper, we use personality variables to understand the underlying motives of women (and men) to enter a competition or avoid it. We use the Big Five personality factors, where especially neuroticism has been related to performance in achievement settings. We first test whether scores on the Big Five are related to performance in our experiment, and second how this is related to incentives. We can show that the sex difference in the willingness to enter a competition is mediated by neuroticism and further that neuroticism is negatively related to performance in competiton. This raises the possibility that those women who do not choose competitive incentives “know” that they should not.